PENERAPAN MODEL PEMBELAJARAN OPEN ENDED PADA PEMBELAJARAN IPS KELAS IV SD NEGERI SUKAKARYA - Sari, Dwi Puspita; Triyogo, Agus; Febriandi, Riduan (Jurnal Ilmiah Aquinas, 2022)
This study aims to determine the completion of social studies learning outcomes for fourth grade students of SD Negeri Sukakarya. The research method used is in the form of a quasi-experimental. The population is all fourth grade students of SD Sukakarya and the research sample is 19 students. Data was collected by using saturated sampling technique. The collected data were analyzed using tests. Based on the results of data analysis with a confidence level of = 5% and dk = 18, it shows that zcount = 2.29 and ztable = 1.64 (zcount > ztable). Thus, it can be concluded that the social studies learning outcomes of fourth grade students of SD Negeri Sukakarya after the implementation of the open ended learning model have been significantly completed. The average value of the final test of students is 72.48 and the percentage of students who complete is 17 students (68.42%). it can be concluded that the social studies learning outcomes of fourth grade students of SD Negeri Sukakarya after the application of the open ended learning model were significantly completed.